FE-Modelling of Composite laminates for Sailboat Masts - Werner, Emanuel; Eriksson, Eric (My University, 2019)
Seldén Mast is a world leading producer of aluminium sail boat masts. The company has also been developing and producing carbon fibre masts and poles for sail boat rigs for the last 20 years. Carbon fibre composites are high-performing and expensive materials, and any improvements made to the layup of the laminates will create a lighter and less expensive product. Seldén’s composite masts are produced with a method called filament winding, where the resin impregnated fibre tows are wound onto a rotating aluminium mandrel with the same shape as the inside of the finished mast. The goals of the project have been to accurately predict the bending stiffness and deflection behaviour of any given mast or pole produced by this method, to evaluate the compressive stiffness and strength of Seldén’s laminates. As well as characterising the micro structure of the carbon fibre laminate in terms of out-of-plane waviness and relating this to the compressive strength of the laminate. A mix of FE analyses using the FEA software LUSAS together with actual benchmark testing has been used to compare simulation to reality. The use of high resolution misalignment analysis (HRMA) has been implemented to characterise the out-of-plane-waviness of the laminates. A method to experimentally determine the compressive strength of a carbon fibre tube has been developed and tested. Comparing the test results to the results from the FE computations shows that it is possible to come within 15% of the actual deflection when using Seldén’s previously obtained material data. There are however signs of asymmetrical bending and stiffness behaviour in non-circular cross-sections. This may occur as a result of the handling of the masts during production, but also due to irregularities in the production technique itself. Strength assessments based on the HRMA were shown to be in good agreement with the experimental values. The method developed in this project to experimentally determine compressive strength of a carbon fibre laminate tube has been shown to give satisfactory results. However, to completely confirm the method, the failure mode of the laminates in the test has to be identified.
Keywords: Maskinteknik; Produktion; Mechanical Engineering; Production